Morphometry Results of Formed Osteodefects When Using Nanocrystalline CeO2 in the Early Stages of Regeneration - Anton V. Lukin; Galina I. Lukina; Alexey V. Volkov; Alexander E. Baranchikov; Vladimir K. Ivanov; Alexey A. Prokopov (International Journal of Dentistry)
This paper studies of the use of nanocrystalline cerium dioxide with artificially formed bone tissue defects. The results of morphometry confirmed the antialterative effect in the early stages of the reparative process of damaged bone tissue. When using calcium hydroxide with nanodispersed cerium dioxide, the nature of osteogenesis should be characterized as activated. In case of damage to the dentin of the roots of the teeth, dentinogenesis in presence of CeO2 occurs with the formation of a combined dentin and bone regenerates. Little or no studies of dentinogenesis in presence of CeO2 were performed by other researchers.